The new international financial architecture and Caribbean OFCs : confronting financial stability discourse - Marshall, Don D. (2007)
Looks at the evolutionary dynamics of the international financial architecture, the norms that make up its economic and cultural habitus, and examines how Commonwealth Caribbean countries, particularly its offshore financial centres, fare in this interaction structure.